Motivation in learning: a case study of young adult learners in Kuala Selangor, Malaysia / Lina Mursyidah Hamzah ... [et al.] - Hamzah, Lina Mursyidah; Sueb, Rosilawati; Alias, Nurul Fitriah; Syed Mustafa, Sharifah Muzlia; Mohd Yusof, Mohammad Mubarrak (Universiti Teknologi MARA, 2022)
This study aims to explore motivation factors that contribute to learning among young adult learners in selected schools in Kuala Selangor, Malaysia. Four focus group discussions had been conducted to collect the data via a semi-structured interview. The selection of participants in the interview was based on learners who experienced the motivational session conducted by the researchers. Using thematic analysis to analyse data, six themes were found in this study. The themes that emerged from the analysis are reasons for coming to school, interest in schooling, disinterest in schooling, subjects of interest, effort to increase academic performance and factors contributing to academic achievement. The findings show that although teachers and friends can be motivating factors that encouraged the learners to go to school, these factors were also hindrances influenced success or failure. Being young adult learners, their cognitive level is still developing and they are influenced by physiological changes. Hence, educators and policy makers need to ensure that young adult learners, especially those who are at risk of dropping out of school, are motivated to complete their secondary education.